2018
DOI: 10.1161/atvbaha.117.310667
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Transitions in Heart Valve Development and Myxomatous Valve Disease

Abstract: Our study demonstrates the heterogeneity of myeloid cells in heart valves and highlights an alteration of macrophage subpopulations, notably an increased presence of infiltrating CCR2+ monocytes and CD206+ macrophages, in myxomatous valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 27 publications
7
68
0
Order By: Relevance
“…This aligns with previous data that murine aging and human disease correlate with M1 polarization, 5,8,45 and that M1 polarization itself promotes cellular calcification. 5,46 This suggests that perhaps differences in macrophage phenotype at baseline in Notch1 +/mice are driving AV phenotypes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This aligns with previous data that murine aging and human disease correlate with M1 polarization, 5,8,45 and that M1 polarization itself promotes cellular calcification. 5,46 This suggests that perhaps differences in macrophage phenotype at baseline in Notch1 +/mice are driving AV phenotypes.…”
Section: Discussionsupporting
confidence: 92%
“…9,44 Here, we have focused on macrophages, which make up the majority of hematopoietic cells in the AV in both health and disease. 8 We have shown that Notch1 +/-AVICs promote macrophage maturation and infiltration, and that macrophages promote AVIC calcification through STAT3-dependent mechanisms (Fig 6).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations